Effect of Base Material Variations on the Characteristics of Briquettes from Coconut Shell Charcoal and Corncob Mixtures - Melenia, Melenia; Ahzan, Sukainil; Pangga, Dwi (Lensa: Jurnal Kependidikan Fisika, 2024)
This study investigates the effects of varying base materials, specifically coconut shell charcoal (ATK) and corncob charcoal (ABJ), on the characteristics of biobriquettes. The research employs an experimental method, analyzing the impact of different ATK and ABJ proportions on calorific value, ash content, moisture content, density, and combustion rate. The biobriquettes were produced by mixing coconut shell and corncob charcoal with 10% tapioca starch adhesive, molded into cubes, and dried. The results show that increasing the ATK proportion improves the calorific value, with the highest value of 10,640 calories in briquettes with 90% ATK. In contrast, higher ABJ content results in faster combustion rates but lower energy efficiency, with the lowest calorific value of 6,424 calories in briquettes containing 90% ABJ. The study also highlights that all biobriquettes meet Indonesian National Standards (SNI) for moisture content and calorific value, although only the 90% ATK sample meets the ash content standard. These findings suggest that coconut shell charcoal is a superior biomass material for producing high-performance biobriquettes, with a 90% ATK and 10% adhesive combination yielding the best overall results for sustainable energy applications.